Leadership Effectiveness and Knowledge Sharing Behavior as Predictors of Job Performance Among Public Elementary School Teachers: a Convergent Design - Cornelio, Grace L. (The Future of Education Journal, 2025)
This study employed mixed methods approach, specifically convergent design, to determine the influence of leadership effectiveness and knowledge sharing behavior on the job performance. The data were gathered from the teachers in the public elementary schools in Region XI, Philippines. Sets of validated adapted survey tools with a five–point Likert scale and interview guide were used to gather data. The statistical tools used to treat the quantitative data were mean, standard deviation and multiple regression analysis, while in the qualitative phase, thematic analysis was employed. In the quantitative phase, results showed that the status of leadership effectiveness and knowledge sharing behavior of teachers were very high, while their status of quality of work life was rated very high also. Further, leadership effectiveness and knowledge sharing behavior significantly influenced the job performance. In terms of lived experiences of participants, as regards the job performance, five themes had emerged, which included fostering a supportive learning community, empowering educators for continuous growth and excellence, cultivating a collaborative professional community, fostering professional development through reflective practice, and promoting inclusive learning. In terms of beliefs, attitudes, and commitment as shaped by their experiences, four themes emerged: striving for excellence, inspiring purposeful practice, embracing continuous improvement, and commitment to growth. Finally, the nature of data integration revealed a merging – converging nature.